Electrical and Recombination Properties of Polar Orthorhombic κ-Ga2O3 Films Prepared by Halide Vapor Phase Epitaxy - Eugene B. Yakimov; Alexander Y. Polyakov; Vladimir I. Nikolaev; Alexei I. Pechnikov; Mikhail P. Scheglov; Eugene E. Yakimov; Stephen J. Pearton (Nanomaterials, 2023)
In this study, the structural and electrical properties of orthorhombic κ-Ga2O3 films prepared using Halide Vapor Phase Epitaxy (HVPE) on AlN/Si and GaN/sapphire templates were studied. For κ-Ga2O3/AlN/Si structures, the formation of two-dimensional hole layers in the Ga2O3 was studied and, based on theoretical calculations, was explained by the impact of the difference in the spontaneous polarizations of κ-Ga2O3 and AlN. Structural studies indicated that in the thickest κ-Ga2O3/GaN/sapphire layer used, the formation of rotational nanodomains was suppressed. For thick (23 μm and 86 μm) κ-Ga2O3 films grown on GaN/sapphire, the good rectifying characteristics of Ni Schottky diodes were observed. In addition, deep trap spectra and electron beam-induced current measurements were performed for the first time in this polytype. These experiments show that the uppermost 2 µm layer of the grown films contains a high density of rather deep electron traps near Ec − 0.3 eV and Ec − 0.7 eV, whose presence results in the relatively high series resistance of the structures. The diffusion length of the excess charge carriers was measured for the first time in κ-Ga2O3. The film with the greatest thickness of 86 μm was irradiated with protons and the carrier removal rate was about 10 cm−1, which is considerably lower than that for β-Ga2O3.